Expression of human alcohol dehydrogenase ADH1B2 in Pichia pastoris and its activity analysis - Tang, Tian-Tian; Zhou, Liang; Ji, Peng-Fei; Bao, Wen-Na; Gong, Xing-Guo (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2012)
Human alcohol dehydrongenase gene ADH1B2 was obtained by RT-PCR using total RNA from liver as template. Recombinant pPICZB-ADHlB2 were constructed and electrotransformed into P. pastoris GS115. DEAE-Sepharose FF was employed to purify the intracellular soluble ADH1B2 protein. Enzyme activity was about 8000 U/mg, influenced by factors like temperature, pH and ion. Plasmid pcDNA3.1-ADH1B2 was constructed and then transfected into human hepatocarcinoma cell Hepg. The transfected Hepg cells showed decreased ROS and consequent decreased Akt phosphorylation, resulting in depressed cell viability. This study may help to get more insights into the relationship between cancer and ADH, and lay theoretical basis for clinic prevention of alcoholism and drug development.